One-way hash function with chaotic dynamic parameters - GUO Wei1; CAO Yang1; WANG Xiao-min2; HE Da-ke1 (Tongxin xuebao)
A novel keyed one-way hash function based on chaotic dynamic parameters was presented which combines the advantage of both chaotic system and conventional one-way hash function.In the proposed approach the fixed parameters of conventional hash function is replaced by chaotic dynamic parameters.Compared with the existing chaotic hash func-tions,the new method takes conventional hash function as essential part of iteration instead of using the message blocks directly in chaotic iteration,thus improves the security of hash function and avoids bringing down system performance at the same time.Theoretical and experimental results show that the proposed method has high performance,strong one way property,large key space,sensitivity to initial conditions and chaotic system’s parameters.